O Cálculo Diferencial e Integral como Ferramenta Indispensável ao Estudo de Modelos de Física Mecânica e as Leis do Movimento Planetário - Mello Filho, Eduardo Jorge Barros de Deus e (2013)
We present the concepts of Di erential and Integral Calculus needed to mathematically model some physics concepts geared to the movement. We also present physical situations that are possible to model the mathematical tools of high school, as well as suggestions for ideas mathematical content of higher education that could be posed to high school students enriching media to discuss these problems more complex physics movement.